EP255/#721 Interval debulking surgery with or without hyperthermic intraperitoneal chemotherapy in advanced-stage ovarian cancer: single-institution cohort study. (4th December 2022) - Lee, Yong Jae; Seon, Kieun; Kim, Jung Chul; Nam, Eun Ji; Kim, Sang Wun; Kim, Sunghoon; Kim, Young Tae; Lee, Jung-Yun
Abstract : Objectives: To evaluate the additive effects of hyperthermic intraperitoneal chemotherapy (HIPEC) to interval debulking surgery (IDS) in patients with advanced-stage ovarian cancer. Methods: From January 2015 to February 2019, 123 patients with stages IIIC-IV ovarian cancer treated with neoadjuvant chemotherapy (NAC) followed by IDS with optimal cytoreduction. 43 patients received IDS with HIPEC and 80 patients had IDS without HIPEC. The median follow-up period was 34.4 months. Results: No differences in baseline characteristics in patients were found between the 2 groups. The IDS with HIPEC group had fewer median cycles of chemotherapy (P = 0.002) than IDS group. The IDS with HIPEC group had higher rate of high surgical complexity score (P = 0.032) and higher rate of complete resection (P = 0.041) compared to IDS group. The times to start adjuvant chemotherapy were longer in IDS with HIPEC group compared to IDS group (P < 0.001). Postoperative grade 3 or 4 complications were similar in the two groups (P = 0.237). Kaplan-Meier analysis showed that HIPEC with IDS group had better progression-free survival (PFS) (P = 0.010), while there was no difference in overall survival between two groups (P = 0.142). In the multivariate analysis, HIPEC was significantly associated with better PFS (HR, 0.60; 95% CI, 0.39 – 0.93). Conclusions: The addition of HIPEC to IDS resulted in longer PFS than IDS without HIPEC not affecting safety profile. Further research is needed to evaluate the true place of HIPEC in the era of targeted treatments.